Contextual ITSM Adoption Across Educational Levels: A University and a Secondary School in Jakarta - Marcel, Marcel; Azhar, Nur Chalik (Universitas Bina Darma, 2025)
This research investigates contextual ITSM adaptation across educational levels through a comparative case study of a university and secondary school in Jakarta. Using qualitative methodology with interviews, observations, and document analysis, we examined implementation patterns at University X (5,000 students, 12 IT staff) and SMA Y (450 students, 2 IT staff). Results show universities achieved semi-formal ITSM maturity levels 2-3 while secondary schools operated at pragmatic levels 1-2, reflecting resource disparities where universities allocated 4% versus 1.5% of operational budgets to IT services. Key findings reveal persistent perception gaps where academic staff predominantly view IT as